(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Right to Information is a basic human right of every human being. The renowned French philosopher Michel Foucault once opined, power is derived from knowledge and information is the basic component of knowledge. Information changes the mentality of people and it is competent enough to cope up with the modern world. The free access to information and participation of people in government decisions develops the transformation of the governance into good governance. So, it is the duty of government to inform citizens about day to day happenings whatever within the government. The parliament of India passed the Right to information act, 2005, to foster Accountability, Transparency, Strengthens the Democratic Principles of Polity and reduces Corruption. This paper tries to highlight the role of RTI in good governance and some recommendations for successful functioning of RTI act.Good Governance is prerequisite for democracy. Such governance includes some factors such as transparency, accountability, rule of law and people’s participation. India is a democratic country and in every democratic country, there is a need of good governance and transparency. In every development administration experiences indicated that there has always an urgent need for improving government .Today in India there is unprecedented corruption at all levels. All feel its pinch but corruption is roaring high. The main factor behind the corruption is secrecy, which was taken as a tool of faithfulness towards government in past era. If we want transparency in governance, there is a need to crack the corruption by cracking the walls of secrecy. The prevalence of corruption, lack of accountability, efficiency and effectiveness demands the requisite changes and transformations to ensure good governance. Information is power and at International level it is recognized that information is essential for development as a result many countries have enacted Right to Information Act. In that direction government of India too introduces a new era of good governance through the enactment of Right to Information Act in 2005.It provide an opportunity to interact with the officials and institutions. Right to Information is a potent weapon to fight against corruption, arbitrariness and misuse of power.RTI has significant bearing on good governance and development. The Right to Information (RTI) is a vital tool for good governance. Transparency and accountability are for good governance. If there is no transparency, accountability cannot be fixed. There should be maximum disclosure and minimum confidentiality. The Main thrust of RTI law is to change the culture of secrecy, red tapism and aloofness that has long plagued India’s monolithic and opaque bureaucracy. Present paper is an endeavor to discuss the major indicators of good governance, role of RTI in good governance and eradication of corruption in India through RTI. Along with that,this paper discusses the position of India in comparison to neighboring countries according to Transparency International (TI) on the basic of governance indicators.